2016
DOI: 10.5194/esurf-4-445-2016
|View full text |Cite
|
Sign up to set email alerts
|

An introduction to learning algorithms and potential applications in geomorphometry and Earth surface dynamics

Abstract: Abstract. "Learning algorithms" are a class of computational tool designed to infer information from a data set, and then apply that information predictively. They are particularly well suited to complex pattern recognition, or to situations where a mathematical relationship needs to be modelled but where the underlying processes are not well understood, are too expensive to compute, or where signals are over-printed by other effects. If a representative set of examples of the relationship can be constructed, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 61 publications
0
13
0
1
Order By: Relevance
“…Realistic synthetic DEMs offer a way to assess and understand geomorphological data, allowing users to proceed with uncertaintyaware landscape analysis to examine physical processes. Valentine and Kalnins (2016) offer an overview about machine learning and its potential in geosciences. Learning algorithms come from the computer science world, and they are designed to replicate the human approach of inferring information from a dataset, and then apply that information predictively.…”
Section: Perspectivesmentioning
confidence: 99%
“…Realistic synthetic DEMs offer a way to assess and understand geomorphological data, allowing users to proceed with uncertaintyaware landscape analysis to examine physical processes. Valentine and Kalnins (2016) offer an overview about machine learning and its potential in geosciences. Learning algorithms come from the computer science world, and they are designed to replicate the human approach of inferring information from a dataset, and then apply that information predictively.…”
Section: Perspectivesmentioning
confidence: 99%
“…Realistic synthetic DEMs offer a way to assess and understand geomorphological data, allowing users to proceed with uncertainty-aware landscape analysis to examine physical processes. Valentine and Kalnins (2016) offer an overview about machine learning and its potential in geosciences. Learning algorithms come from the computer science world, and they are designed to replicate the human approach of inferring information from a data set, and then apply that information predictively.…”
Section: Perspectivesmentioning
confidence: 99%
“…The slope, aspect, curvature, and relative position of features and terrain variability were the derived secondary features of the bathymetry and backscatter datasets [36,37]. Some previous studies suggested a range of secondary features that were possibly associated with substrate types from terrain analysis, which includes the bathymetric position index (BPI), roughness, curvature, aspect, Moran's I, and Sobel filter [28][29][30]. BPI is the vertical difference between a cell and the mean of the local neighborhood [36], which is deemed to be significant for sediment transport under the effect of waves and currents.…”
Section: Primary and Secondary Datamentioning
confidence: 99%